Response of a CMS HGCAL silicon-pad electromagnetic calorimeter prototype to 20–300 GeV positrons. (1st May 2022) - ,; Acar, B.; Adamov, G.; Adloff, C.; Afanasiev, S.; Akchurin, N.; Akgün, B.; Khan, F.A.; Alhusseini, M.; Alison, J.; Alpana, A.; Altopp, G.; et al.
Abstract: The Compact Muon Solenoid collaboration is designing a new high-granularity endcap calorimeter, HGCAL, to be installed later this decade. As part of this development work, a prototype system was built, with an electromagnetic section consisting of 14 double-sided structures, providing 28 sampling layers. Each sampling layer has an hexagonal module, where a multipad large-area silicon sensor is glued between an electronics circuit board and a metal baseplate. The sensor pads of approximately 1.1 cm 2 are wire-bonded to the circuit board and are readout by custom integrated circuits. The prototype was extensively tested with beams at CERN's Super Proton Synchrotron in 2018. Based on the data collected with beams of positrons, with energies ranging from 20 to 300 GeV, measurements of the energy resolution and linearity, the position and angular resolutions, and the shower shapes are presented and compared to a detailed Geant4 simulation.